Stanisław Józef Leonard Szober (6 XI 1879 – 29 VIII 1938) - Dulna-Rak, Ewa (Idiolekty, 2025)
This article presents the life and academic legacy of Stanisław Szober, a distinguished linguist. It discusses his primary research areas, which included Polish syntax, language teaching methodology, linguistic correctness, and usage standards. Among his many works on diverse topics, particular attention is given to his exploration of individual language. Although Szober published only one study that can be considered a methodological description of an idiolect, his interest in the subject can be traced back to his earliest articles.